A Castaway's Look. The Writing of the Wreck-Metaphor in Catherine Pozzi's Diaries (Global Journal of Human-Social Science, 2020)
is a remarkable figure of the late 19 th century and the period between the World Wars. In 1893, at the age of 13, she won a little notebook from her grandmother and started a diary-writing practice she maintained until the end of her life, except for a few interruptions. This research stands at the intersection between intellectual history and literary studies. It is focused on the role played by the "castaway" image, developed by Pozzi as a self-reflexive construction in her diary. As a reflexive and metaphorical image, her castaway's wreck draws from three main motifs, which are noticeable in her self-referential discourse: the sadness of an ill-fated love affair with one of the most celebrated men of French intelligentsia, namely Paul Valéry; the impact of tuberculosis on her body; and a frustrated intellectual vocation. Based on Hans Blumenberg's views about metaphors and dialoguing with his theoretical construction, I sought to understand how a self-referential statement acts on a discourse by resorting to the textual composition of a metaphorical image, in order to be capable of representing the experience of a painfully stimulated conscience. This image emerges as an intimate and unique element, which can be interpreted as Pozzi's entries accept the wreck image as the reflexive form of a metaphorical destiny.
Keywords: self-referential discourse; metaphor; selfreflexivity; catherine pozzi